The Influence of Transactional and Transformational Leadership Styles of Ward Heads on Patient Safety Culture Implementation in a Regional Hospital in Indonesia - Rafi, Muhammad; Saafi, La Ode; Risky, Sartini (Magister Kesehatan Universitas Mandala Waluya, 2026)
Introduction: Patient safety culture is an indicator of service quality and a system that makes patient care safer. The leadership style of the head of the ward is one factor that influences the implementation of a patient safety culture. Indonesia is still struggling to improve the quality of healthcare services by enhancing the patient safety culture among care professionals, including nurses. This study aims to examine the influence of the Head of Room's transactional and transformational leadership style on the implementation of a patient safety culture in the Regional Public Service Agency, Benyamin Guluh Hospital, Kolaka Regency. Method: Qantitative approach with a cross-sectional design was used, this study took place during July 2024. Involving 140 respondents, consisting of team leaders and nurses working in inpatient care. Result: The positive influence of transformational leadership style (0.332 (positive direction), T statistic 2.665 and p-value 0.008) and laizzes faire (0.309 (positive direction), T statistic 2.828 and p-value 0.005) in the implementation of patient safety culture. Conclusion: This study emphasizes the importance of a ward head's leadership style that supports a patient safety culture, particularly in reporting individual performance indicators and implementing employee work targets. It is recommended that hospitals improve the implementation of a patient safety culture by conducting continuous patient safety rounds, supervising, monitoring, and evaluating the implementation of individual performance indicators, and encouraging staff to report.